Migration of a Broken Kirschner Wire from Lateral End of Clavicle to the Cervical Spine - Tamrakar, Rojan; Chapagain, Dinesh (Journal of Nepal Health Research Council, 2020)
Kirschner wire (K-wire) is commonly used in orthopaedics to treat various fractures. Migration of K-wire from the shoulder to different vital organs have been documented in many case reports. The possible explanations for such migration have been mentioned in the various literatures with the recommendations to prevent such complication. We report a case of migration of a broken K-wire to the cervical spine, which was used for the treatment of displaced lateral end fracture of right clavicleKeywords: Cervical spine; kirschner wire; migration,